DRUG UTILIZATION PATTERN AMONG GERIATRIC PATIENTS ADMITTED IN MEDICAL INTENSIVE CARE UNIT IN A TERTIARY CARE TEACHING HOSPITAL - V, Balaji; Aithal, Sathisha; S, Geetha; Es, Swetha (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Objective: This study aims to evaluate the drug utilization pattern in terms of defined daily dose (DDD) among geriatric patients admitted in medical intensive care unit (MICU) of a tertiary care hospital. Methods: Retrospective medical record analysis was performed for the geriatric patients (age ≥65 years) admitted in MICU from 1st January 2012 to 30th June 2012. The relevant data were collected in a proforma. The drugs were categorized by anatomical therapeutic classification and their DDD was calculated. Results: Diabetes mellitus was the most common cause for admission. Parenteral preparations (51.12%) constituted the largest share among all the drugs prescribed. Pantoprazole - A02BC02 with DDD 25.3 was the most commonly prescribed parenteral drug (23.5%). Amlodipine - C08CA01 with DDD 29.0 was the most commonly prescribed oral drug (27.6%). Average number of drugs per patient was 9.37±0.27. Average number of antimicrobials prescribed per patient was 1.26±0.09. Ceftriaxone was the commonly prescribed antimicrobial drug. Conclusion: This study shows the most common causes of admission among geriatric patients in MICU setup and the pattern of drugs used. Drug utilization studies of this type may ultimately help in improving the quality of healthcare given to the geriatric patients. Keywords: Anatomical therapeutic chemical classification, Defined daily dose system, Drug utilization pattern, Geriatric patients.